SPORTS TRAINING IN SUMMER POLYATHLON BASED ON THE RATIONAL DISTRIBUTION OF TRAINING LOADS - Nikiforova, O.N.; Markin, E.V.; Sorokin, D.V.; Khoteeva, M.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the rationality of the distribution of training loads of different types of all-around exercises of polyathlon students in the annual cycle. Methods and structure of the study. To solve the set goal, a pedagogical experiment was conducted, in which 32 polyathlete students aged 17-24 years old (men and women) with qualifications from the II sports category to masters of sports, involved in sports improvement sections of various universities in Moscow, took part. All students-polyathletes were divided into two equal groups - experimental and control. The experimental group (16 people) practiced according to the developed methodology, taking into account the patterns of transfer (interaction) of physical qualities and the mutual influence of various types of exercises. In the control group (16 people), they did not adhere to a strict sequence of classes and included in one lesson a variety of exercises included in the types of all-around. Results and conclusions. The results of control tests and competitions showed that the increase in results in all types of all-around events for the entire experimental period was significantly higher in the groups that used the developed methodology, which provided for the consistent use of exercises, taking into account the transfer of physical qualities during two training sessions a day. The rational distribution of training loads in the annual cycle allowed to improve sports results in 100% of polyathletes students, and in 50% of cases to achieve sports standards and titles.